PERANCANGAN APLIKASI BERBASIS KNOWLEDGE MANAGEMENT UNTUK MEMONITORING PRESTASI AKADEMIK MAHASISWA PADA INFORMATICS BUSINESS INSTITUTE (IBI) DARMAJAYA - Karnila, Sri; -, Nurfiana (Jurnal Informatika, 2016)
Â The design of knowledge management based applications to monitor this academic achievement facilitated interface in the form of Applications used by the manager of academic achievement in Higher Education. Students academic achievement is generally shown through the evaluation results in final form with GPA, as well as at Informatics Business Institute (IBI) Darmajaya. IBI Darmajaya to produce competent graduates in their field is not enough just to provide learning support facilities such as adequate facilities and infrastructure, reliable lecturers, good curriculum, and scholarship facilities. Application Monitoring academic achievement is needed so that IBI Darmajaya can continue to control the increase or decrease in student achievement so that it can pass on time. Therefore, the design of knowledge management based applications for monitoring academic achievement as an interface in the management of academic achievement is needed. With the stages of SDLC, knowledge management system will provide convenience in the design of applications, so the application produces information that becomes knowledge for IBI Darmajaya and the manager in particular can monitor academic achievement, controlling the increase in student achievement in each semester, so that students are motivated to learn and pass appropriately time. Applications with the right information search attempt to motivate the CPI to remain above the average provisions, to provide a CPK report to parents and management of scholarship managers.Â Keywords: Application Design, Knowledge management, academic achievement, IPK